Impact of Lime, Phosphorus, and Potassium on Yield and Forage Quality on Native Hay Meadows in Southeast Kansas - Junior I. Yasuoka; Wendie Powell; Walter H. Fick; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
Native meadows are frequently harvested for hay in southeast Kansas to produce forage for winter use. However, the low soil fertility associated with nutrient removal has resulted in limited yield potential and broomsedge infestation. This study evaluated the effect of phosphorus, potassium, and lime on the forage yield and quality in a native meadow. Our results indicated that P and K fertilization contributes to improving yield and quality on native meadows in southeast Kansas. This study will be repeated in 2023, including broomsedge measurements.
Keywords: biomass; crude protein; quality; weed control